Determinants of Women Participation in Business Start-ups: Empirics of Motivators, Challenges and Opportunities (Global Journal of Management and Business Research, 2021)
A study of women entrepreneurship remains highly limited in the extant literature. Perhaps this has contributed to the slow growth of women-led start-ups, particularly in the developing economies. 1 Although several (prior) studies have hinted some peculiar characteristics defining the roles and growth potentials of women entrepreneurs in other parts of the world, there is yet a limited study in the field particularly in the Gambia. Consequently, this study seeks to address this gap by identifying the challenges, and opportunities experienced by women entrepreneurs in the Gambia. To do this, we employed a qualitative study of randomly selected businesswomen in three regions. The findings showed that women entrepreneurs experienced various challenges, including, access to finance, lack of government support, limited access to equipment or working materials, poor infrastructure problem, cumbersome regulations, and tax obligations. Moreover, our study reported the existence of fewer opportunities for women business operators such as the availability of entrepreneurship training programs, and business registration processes.